Analisis Kinerja Ruas Jalan Akibat Adanya Pusat Perbelanjaan (Studi Kasus KPD Swalayan Jalan Rajawali Palangka Raya) - Norce Lumbantoruan; Murniati Murniati; Salonten Salonten (Media Ilmiah Teknik Sipil, 2021)
Palangka Raya is the economic center of Central Kalimantan Province, where there are many shopping centers that offer goods at low prices, one of which is the Koperasi Persekutuan Dayak Swalayan which sells daily necessities at low prices and is always visited by consumers so that there is an increase in traffic and tends to result in increased traffic conflict over traffic that is right in front of KPD Swalayan. In this study using two data, namely secondary data and primary data which were analyzed using the PKJI 2014 method. From the results of the analysis of the the percentage of traffic pull due to the KPD Swalayan burdening Jalan Rajawali by 4.34%, the existence of KPD Swalayan results in changes in the performance of roads based on the Degree of Saturation (DJ) = 0,60, Capacity (C) = 1859,70 skr/hour before KPD Swalayan operates after KPD Swalayan operates Degree of saturation (DJ) = 0,57, Capacity (C) = 1859,70 skr/hour, and if the KPD Swalayan is considered non-existent then the side barriers that occur will be reduced so that the Degree of Saturation (DJ) = 0,55, Capacity (C) = 1921,69skr/hour.